Implementasi Iso 9001:2008 dalam Mengembangkan Budaya Mutu Madrasah - Moh. Zainal Fanani (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2017)
The government take serious act to enhance quality of education either public or private school. One of famous way used by education organization is adopting international based quality management system. One of international based quality standard about Quality Management System is ISO 9001:2008, customer oriented quality management system. Application of Quality Management System ISO 9001:2008 in education service is the right momentum to fix quality of education especially madrasah. Application of Quality Management System ISO 9001:2008 in education organization are meant to enhance customer’s satisfaction through education organization, build awareness about the urgency of prime service to customer, teach education organization so they loyal to agreeable things, and prepare quality document. The successful of Quality Management System ISO 9001:2008 implementation affected by culture own by madrasah. Sincerity is needed to facilitate and manage culture changes into quality culture.